On-Line Compensation for the Disturbance Rejection Rate of a Platform Seeker Based on a High-Gain Extended State Observer - Li Wei; Liu Shixiang; Zhang Wenjie; Xia Qunli (International Journal of Aerospace Engineering)
This paper focuses on the on-line compensation of the disturbance rejection rate (DRR) for a platform seeker. The mathematical model of the typical platform seeker based on the inertial space is established, and the line-of-sight (LOS) rate from different signal extraction points is strictly derived. Considering the spring torque disturbance and damping torque disturbance caused by the missile attitude motion, the seeker DRR transfer functions are deduced and the amplitude and phase characteristics at different frequencies are also analyzed. In order to close the engineering practice, the DRR parasitic loop (DRRPL) model of the seeker is rationally simplified and the stable region of the parasitic loop from different extraction points is also obtained. However, to increase the stability and guidance accuracy of the missile terminal flight, the compensation scheme based on the high-gain extended state observer (ESO) is used to estimate the disturbance torques and eliminate the seeker DRR effect. Numerical simulations are conducted to verify the effectiveness of the proposed scheme. The simulation results show that the seeker DRR effect mainly exists in the middle and low frequencies and the stable region of the parasitic loop at different signal extraction points is different. The proposed compensation scheme can effectively eliminate the parasitic loop effect of the seeker and increase the flight stability of the missile. It can reduce the terminal miss distance of the missile and improve the strike accuracy.